Measurement of serum ACE status may potentially improve the diagnosis of SARS-CoV-2 infection - Gcinokwakhe D Ngcobo (Elsevier, 2021)
The severity of SARS-CoV-2 infection is associated with underlying cardiovascular or pulmonary pathological conditions. The fatality rate of this typical pneumonia has superseded the two previous coronavirus epidemics combined. Thus far, comprehensive diagnosis of SARS-CoV-2 remains essential for effective screening, detection, and disease monitoring. This allows employment of different life-saving interventions to lower the spread and mortality, whilst the development of labelled therapeutics is underway. In this perspective, the measurement of Angiotensin-converting enzyme (ACE) status is perceived as a potential prognostic biomarker for SARS-CoV-2 patients. This notion is based on the observation that SARS-CoV-2 infection via attachment to Angiotensin-converting enzyme-2 (ACE2) receptor, downregulates ACE2 expression. Thus leading to the inability to efficiently counter-regulate the damaging effects of its homolog; ACE. The perspective is further strengthened by the recommendations of therapeutics that attenuate the conversion of Angiotensin I to a vasoconstrictor; Angiotensin II as an effective treatment of SARS-CoV-2 infection. In addition, other off-labelled used drugs target the latter; restoration of multiple organ failure and or cytokine storm inhibition. Therefore, this suggests that ACE may be strongly implicated in the pathogenesis of SARS-CoV-2.